If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -7 + 2 = 2z Reorder the terms: -7 + 2 + 3b = 2z Combine like terms: -7 + 2 = -5 -5 + 3b = 2z Solving -5 + 3b = 2z Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3b = 5 + 2z Combine like terms: -5 + 5 = 0 0 + 3b = 5 + 2z 3b = 5 + 2z Divide each side by '3'. b = 1.666666667 + 0.6666666667z Simplifying b = 1.666666667 + 0.6666666667z
| (8x-10)=7x | | f(f(x))=25x-18 | | -2x+7x-4x=0 | | 6.3=9.8-0.5x | | 3(6y-2)+(3y+4)= | | -4(x-3)=-12 | | 4x-3.7=-8x-2.1 | | -6x=-4x-15 | | 4(5-3)=12 | | 3b-7+2=2z(b) | | 10=1/3(x-15) | | 6X-8+10=6X+20 | | (3x+10)+y=180 | | -3(7q+4)-5= | | 10=13(x-15) | | -5(z+1)=7-4z | | 3x+3x-7=35 | | 6y+6y=108 | | 5-7=5+2 | | 5-a=12 | | y=8x^3-2x | | 180-2(x+20)=x-10 | | 0=-5t^2+7t-2 | | 5/8x-10=5/4x | | -(5x-6)=2 | | -2/5w=-4/5 | | 11h-14=52 | | 5(2+4b)=60 | | 4-2(x+3)=8 | | 13+40x-72=21 | | -84=(x*x)-19x | | 5.8+3.6(x-4)=9.3 |